Gastric volvulus: a rare cause of gastric outlet obstruction in pediatric age - Güven, Burcu; Beger, Burhan; Uslu, Enver; Düz, Ebüzer (The European Research Journal, 2019)
Gastric volvulus is a rare disease in the pediatric population. Symptoms may change depending on the type of the disease, rotation degree, and the etiology. Early diagnosis and treatment are important especially in the acute type of the gastric volvulus. Here, it was presented a 10-month-old girl with non-bilious vomiting and abdominal distention in last 2 days, diagnosed gastric volvulus.